PEMBERDAYAAN REMAJA DALAM OPTIMALISASI PENINGKATAN PENGETAHUAN TENTANG KESEHATAN REPRODUKSI REMAJA MELALUI PROGRAM KELOMPOK REMAJA DI DUSUN BALANGGAR PAKONG PAMEKASAN - Qurratul A’yun; Yayuk Eliyana; Layla Imroatu Zulaikha (BADAN PENERBIT STIEPARI PRESS, 2022)
Lack of knowledge, nature and risk behavior in adolescents that have an impact on adolescent reproductive health status requires the availability of adolescent care health services that can meet adolescent health needs, especially services for adolescent-friendly reproductive health. The target of this community service activity is the group of teenagers in the Hamlet of Bajuang Pakong, Pamekasan, who are teenagers. The purpose of this activity is to increase the knowledge and understanding of adolescents about reproductive health and to empower adolescents through the Youth group program as a forum for adolescents to increase knowledge about reproductive health. This group of teenagers shared with other teenagers during women's activities, then these teenagers made applications on social media as a means to provide information to make it easier to provide information to other peers. With the Youth group program, students are enthusiastic about seeking health information for adolescents and find it useful to have this youth group program.